Liquid Phase Separation Mechanism of Cu-40 wt.% Pb Hypermonotectic Alloys - Xiaosi Sun; Weixin Hao; Teng Ma; Junting Zhang; Guihong Geng (Advances in Materials Science and Engineering)
Solidification microstructures of Cu-40 wt.% Pb alloy were examined under different undercooling degrees. The liquid phase separation mechanism in the systems with stable miscibility gaps mainly involved Ostwald ripening, Brownian motion, Marangoni migration, and Stokes motion. Stokes had little influence on the liquid phase separation in the early phase and played a leading role in the later period. The liquid phase separation mechanism of Cu-40 wt.% Pb hypermonotectic alloy was illustrated in detail.